The life and activity of Vaclovas Biržiška in 1940 - 1945 - Stakulienė, Silvija (Knygotyra, 1997)
V. Biržiška’s activities are noted in the archival documents that can be found in the manuscripts departments of the libraries of Vilnius University and the Academy of Sciences, as well as in the Central State Archives. On January 1, 1940, V. Biržiška was elected the director of Vilnius University Library. At the same time, he managed the library of Vytautas the Great University. As the director of Vilnius University Library, V. Biržiška prepared new rules for readers on how to use the library, attended to the librarians’ financial matters, and sought better premises. On his own initiative, on September 1, 1940, the Chair of Bibliography was established in the Faculty of Humanitarian Sciences, with V. Biržiška elected as chairman. The plan and teaching program were prepared, but World War II interrupted all his projects. After the Germans occupied Lithuania, V. Biržiška went through a very complicated period in his life. Unable to manage the two major libraries of Lithuania, he retired from his duties as director of Vilnius University Library on November 28, 1941. He then went to Kaunas and managed the Vytautas the Great University Library. Only a personality like V. Biržiška could manage the two greatest libraries in 1940-1941 during such a difficult period in the history of Lithuania.